Effect of Storage and Weight of Egg on Post-Hatching Performance of Local Ducks - Mahmood, Shakhawan Noori; Al-Karkuki, Shahla Mohammed Saeed (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The effect of treatments: storage time (0, 3, and 7 days), and egg weight (small<58 g; medium: 57.99 – 64.99 g; large> 65 g) on the performance of local ducks were studied. Incubation of 785 eggs was carried out in a commercial incubator and after hatching 162 ducklings were weighed and distributed into nine treatments (18 ducks each). Live body weight, feed intake, weight gain, and feed conversion ratio were recorded during the experiment period of 42 days. Results showed that at all periods the live body weight of ducks from large eggs was significantly (p<0.05) and numerically heavier compared with ducks from the medium and small eggs of the three storages. While the ducks from T12 were significantly or numerically higher feed intake compared with other treatments at all periods. The weight gain and feed conversion ratio were also significantly affected by treatments vibratory in different periods. Generally, Duck from T22 at (1-7 and 36-42) day, T12 at (8-14) day, T11 and T21 at (15-21) day, and T33 at (22-28) day had significantly higher weight gain. Ducks from T23 at (8-14) day, T33 at (15-21) day, T21 and T23 at (22-28) day and T13 at (36-42) had significantly and numerically lower feed conversion ratios. Since optimum duckling performance can only be achieved when chicks hatch from egg weights were considered according to storage times.